2017
DOI: 10.1016/j.mri.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Renal plasma flow (RPF) measured with multiple-inversion-time arterial spin labeling (ASL) and tracer kinetic analysis: Validation against a dynamic contrast-enhancement method

Abstract: Purpose-To propose and validate a method for accurately quantifying renal plasma flow (RPF) with arterial spin labeling (ASL).Materials and methods-The proposed method employs a tracer-kinetic approach and derives perfusion from the slope of the ASL difference signal sampled at multiple inversion-times (TIs). To validate the method's accuracy, we performed a HIPAA-compliant and IRB-approved study with 15 subjects (9 male, 6 female; age range 24-73) to compare RPF estimates obtained from ASL to those from a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Our ASL values for cortical renal perfusion are in agreement with those obtained at 3 T using breath-hold multi-TI sequences: 151 ± 37 to 215 ± 65 ml/min/100 g [20,21], but even in healthy volunteers at this field strength single-TI values range between 229 ± 41 to 327 ± 63 ml/min/100 g [10,11,26]. This variation can be attributed to different acquisition schemes, kinetic models and study populations.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our ASL values for cortical renal perfusion are in agreement with those obtained at 3 T using breath-hold multi-TI sequences: 151 ± 37 to 215 ± 65 ml/min/100 g [20,21], but even in healthy volunteers at this field strength single-TI values range between 229 ± 41 to 327 ± 63 ml/min/100 g [10,11,26]. This variation can be attributed to different acquisition schemes, kinetic models and study populations.…”
Section: Discussionsupporting
confidence: 84%
“…Previous work has relied on acquiring data at multiple inversion times during separate breath-holds at 3 T [20,21], or using prospective respiratory gating at 1.5 T [22,23]. The disadvantage of prospective gating is that it prolongs acquisition time unnecessarily if separation of respiratory phases is not required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutajar et al 24 showed that for a group of healthy subjects, ASL-measured renal blood flow was comparable to contrast-enhanced measures (263±41 vs 287±70 ml/min/100g), and had better day-to-day reproducibility than the latter. Conlin et al 25 performed the comparison between ASL and the contrast-enhanced method in both healthy subjects and patients with estimated GFR 46–93 ml/min. The averaged difference between RPF measured by the two methods was 9 ml/min.…”
Section: Non-contrast Mrimentioning
confidence: 99%